A Novel approach for Asynchronous Microprocessor Design and its Implementation on FPGA - Rani, Archana; Grover, Naresh (Bulletin of Electrical Engineering and Informatics, 2019)
The asynchronous processors have a number of advantages, especially in SoC (System on chip) including reduced crosstalk between analog and digital circuits, ease of integrating multi-rate circuits, ease of component reuse and less power consumption as well. This paper presents processor architecture design, its implementation followed by processor instruction set, data path flow for fetching unit, Register type, I-type and load /store type instruction flow. Thereafter this paper illustrates control unit design of processor that shows the controlling of signals for different units in processor design. Further, a complete internal structure is shown followed by features of novel processor architecture. It has capability of handling even I-Type, R-Type and Jump instructions with multiplier instruction packet. Moreover, it uses separate memory for instructions and data read-write that can be changed at any time.In the end, results have been shown using implementation windows. The complete design has been written using VHDL and then simulated and synthesized by XILINX ISE tool.